An efficient heterogeneous Ni/Ni2P catalyst for urea-assisted water electrolysis. Issue 68 (5th August 2022) - Li, Jiaxin; Sun, Sijia; Yang, Yun; Dai, Yunrong; Zhang, Baogang; Feng, Ligang
Abstract : Built-in electrophilic/nucleophilic domains promoted the favorable adsorption of urea molecules on the surface/interface of heterogeneous Ni/Ni2 P for urea oxidation. Abstract : Built-in electrophilic/nucleophilic domains promoted the favorable adsorption of urea molecules on the surface/interface of heterogeneous Ni/Ni2 P for urea oxidation.